Oxford textbook of spirituality in healthcare - Cobb, Mark; Puchalski, Christina M.; Rumbold, Bruce D. (Oxford Oxford University Press, 2012)
Spirituality and healthcare is an emerging field of research. Healthcare organisations and practitioners are therefore challenged to understand and address spirituality, to develop their knowledge and implement effective policy. This reference text on the subject provides a comprehensive overview of key topics.
Medicine and religion: a historical perspective / Gary B. Ferngren -- Buddhism: perspectives for the contemporary world / Kathleen Gregory -- Chinese religion: Taoism / Russell Kirkland -- Christianity / Alister E. McGrath -- Feminist spirituality / Susan A. Ross -- Indian religion and the Ayurvedic tradition / Prakash N. Desai -- The Western humanist tradition / Stan van Hooft -- Indigenous spiritualities / Graham Harvey -- Islam / Abdulaziz Sachedina -- Judaism / Dan Cohn-Sherbok -- "New Age" spirituality / Paul Heelas -- Philosophy / Graham Oppy -- Secularism / Trevor Stammers, Stephen Bullivant -- Sikhism / Eleanor Nesbitt -- Healthcare spirituality: a question of knowledge / John Swinton -- Personhood / Rosalie Hudson -- Belief / Mark Cobb -- Hope / Jaklin Eliott -- Meaning making / Laurie A. Burke, Robert A. Neimeyer -- Compassion: luxury or necessity? / Carol Taylor, Susan Walker -- Dignity: a novel path into the spiritual landscape of the human heart / Shane Sinclair, Harvey M. Chochinov -- Cure and healing / Lodovico Balducci, H. Lee Modditt -- Suffering / Betty Ferrell, Catherine Del Ferraro -- Ritual / Douglas J. Davies -- Culture and religion / Peter van der Veer -- Models of spiritual care / Bruce Rumbold -- Healthcare chaplaincy / Chris Swift, George Handzo, Jeffrey Cohen -- Complementary, alternative, and integrative medicine / Margaret L. Stuber, Brandon Horn -- Restorative medicine / Christina M. Puchalski -- Nursing / Wilfred McSherry, Linda Ross -- Faith community (parish) nursing / Antonia M. van Loon -- Psychiatry and mental health treatment / James L. Griffith -- Social work / Margaret Holloway -- Care of children / Patricia Fosarelli -- Care of elderly people / Elizabeth MacKinlay -- Palliative care / Jackie Ellis, Mari Lloyd-Williams -- Spirituality and the arts: discovering what really matters / Nigel Hartley -- Care of the soul / Michael Kearney, Radhule Weininger -- Counselling / William West -- Dignity conserving care: research evidence / Shane Sinclair, Harvey M. Chochinov -- Pastoral theology in healthcare settings: blessed irritant for holistic human care / Emmanuel Y. Lartey -- Next steps for spiritual assessment in healthcare / George Fitchett -- Methodology / David Hufford -- Measures / Arndt BËussing -- On the links between religion and health: what has empirical research taught us? / Hisham Abu-Raiya, Kenneth I. Pargament -- Quality of life / Bella Vivat -- Cognitive sciences: a perspective on spirituality and religious experience / Kevin S. Seybold -- Spiritual Well-Being Scale: mental and physical health relationships / Raymond F. Paloutzian, Rodger K. Bufford, Ashley J. Wildman -- Prayer and meditation / Marek Jantos -- Resiliency and coping / Gregory Fricchione, Shamim Nejad -- Spiritual experience, practice and community / Fiona Gardner -- Policy / Bruce Rumbold, Mark Cobb, Christina M. Puchalski -- Healthcare organizations: corporate spirituality / Neil Pembroke -- Utility and commissioning of spiritual carers / Lindsay B. Carey -- Social care / Holly Nelson-Becker, Mary Pat Sullivan -- Curriculum development in spirituality and health in the health professions / Christina M. Puchalski, Mark Cobb, Bruce Rumbold -- Clinical Pastoral Education / Angelika A. Zollfrank, Catherine F. Garlid -- Competences in spiritual care education and training / Ewan Kelly -- Guidance from the humanities for professional formation / Nathan Carlin, Thomas Cole, Henry Strobel -- Training and formation: a case study / Fiona Gardner -- Interdisciplinary teamwork / Peter Speck -- Ethical principles for spiritual care / Daniel P. Sulmasy -- Contemporary spirituality / David Tacey -- The future of religion / Grace Davie, Martyn Percy -- The future of spirituality and healthcare / Mark Cobb, Bruce Rumbold, Christina M. Puchalski.
Internet access card bound inside front matter.
Includes bibliographical references and index.
Keywords: Medical care -- Religious aspects; Health -- Religious aspects